2019
DOI: 10.1016/j.jas.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling organic residue analysis, faunal, archaeobotanical and historical records: Diet and the medieval peasant at West Cotton, Raunds, Northamptonshire

Abstract: Information on medieval diet and subsistence practices has traditionally been compiled from a combination of documentary sources, faunal and archaeobotanical assemblages, together with other information gained from archaeological excavations. Much is known of high status medieval dietary practices but less about what foodstuffs the medieval peasantry consumed.Here, we examine the everyday dietary practices of people living in a small medieval manor and associated hamlet at West Cotton, Raunds, Northamptonshire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…A further question raised by this study is the near absence of dairy products found in vessels from both sites and all phases (n = 3, 5%), suggesting the vessels were not used to either heat milk or produce butter, cream or cheese from milk. This stands in contrast to a lipid residue study of late Saxon to early medieval pottery (AD 950 to 1450) from rural West Cotton, Northamptonshire (Dudd and Evershed 1998;Dunne et al 2019), where dairy products were shown to play a significant part in the peasant diet (c. 25%). However, West Cotton was an agricultural community, growing crops and managing cattle, sheep and pigs, and dairy products, sometimes referred to as 'white meats' of the poor, are thought to have been mainstays of the medieval peasant's diet (Woolgar 2016).…”
Section: Discussioncontrasting
confidence: 88%
“…A further question raised by this study is the near absence of dairy products found in vessels from both sites and all phases (n = 3, 5%), suggesting the vessels were not used to either heat milk or produce butter, cream or cheese from milk. This stands in contrast to a lipid residue study of late Saxon to early medieval pottery (AD 950 to 1450) from rural West Cotton, Northamptonshire (Dudd and Evershed 1998;Dunne et al 2019), where dairy products were shown to play a significant part in the peasant diet (c. 25%). However, West Cotton was an agricultural community, growing crops and managing cattle, sheep and pigs, and dairy products, sometimes referred to as 'white meats' of the poor, are thought to have been mainstays of the medieval peasant's diet (Woolgar 2016).…”
Section: Discussioncontrasting
confidence: 88%
“…Our findings may be compared with the only other study of residues from the Conquest period, of the rural manorial complex of West Cotton, Raunds, Northamptonshire [30,31]. Here, organic residues from 73 vessels (123 sherds) spanning the pre-Conquest (AD 950-1150), manorial (AD 1100-1250) and manor/hamlet (AD 1250-1400) phases revealed evidence for preparation of predominantly ruminant products, alongside leafy vegetables including biomarkers for the Brassica and Allium genera.…”
Section: Plos Onementioning
confidence: 74%
“…The tenements were progressively abandoned throughout the fourteenth century, and by the mid-fifteenth century the settlement was uninhabited and given over to pasture closes (Figs. 2 and 3: Dunne et al 2019).…”
Section: The West Cotton Projectmentioning
confidence: 99%
“…As noted above, organic residue analysis has long contributed to a wide range of archaeological questions but is best known for its contribution to elucidating diet and animal management strategies worldwide (e.g. Copley et al 2003;2004;2005a;2005b;2005c;Craig et al 2003;Evershed et al 2008;Outram et al 2009;Dunne et al 2012;Salque et al 2012;Cramp et al 2014a;2014b;Craig et al 2015;Heron et al 2015;Smyth and Evershed 2015;Debono Spiteri et al 2016;Dunne et al 2017;Ethier et al 2017;Mileto et al 2017;Whelton et al 2018;Cramp et al 2019;Dunne et al 2019). Organic residue analysis of pottery has also produced valuable insights into many ceramic characteristics, including manufacture, incorporating decoration, sealing and repair (Charters et al 1993a;Urem-Kotsou et al 2002;Regert et al 2003;Connan et al 2004;2013;Knappett et al 2005;Connan et al 2008;Stern et al 2008;Stacey et al 2010), and use, for example, vessel specialisation (Mottram et al 1999;Copley et al 2005a;Cramp et al 2011;Salque et al 2013;.…”
Section: Overviewhow Organic Residue Analysis Provides Insights Into Vessel Functionmentioning
confidence: 99%
See 1 more Smart Citation